Vásquez Pinango, Erika Beatriz. Intento autolítico en población amazónica, Hospital José María Velasco Ibarra, Tena, 2021 - Vásquez Pinango, Erika Beatriz (2022)
ABSTRACT: The increase in suicides at a national and global level has led to a greater emphasis on mental health care in order to improve strategies for suicidal behavior. In emergency care, various staging, such as the Sad Persons scale, are used to determine the imminent risk and provide support or decontamination treatment, especially in cases of self-inflicted poisoning. This study aims to determine the incidence of suicide attempts in the Amazonian population treated at Hospital General José María Velasco Ibarra from January to December 2021. It develops a cross-sectional, retrospective investigation with an explanatory and descriptive approach based on adequately addressing the research problem. Of 34 patients with ICD-10 descriptions from X60 to X84, the average age was 29.7 years, and the female gender stands out with 52.9% of suicide attempts. 61.8% of the entire population is indigenous, with a secondary level for the most part. The male gender, 40%, had a habitual consumption of alcohol, tobacco, or drugs, the female gender, 38.9%, and a single transgender case. Of these, family problems are 17.6%, couple problems 14.7%, and symptoms associated with affective disorders are the most outstanding risk factors. More research is required on suicide attempts according to their ethnic groups to understand their cultural, historical, and political contexts, as well as the positive or negative influence as a risk or protective factor in the modification of suicidal behavior in the adult population.